Recoverable peroxidase-like Fe3O4MoS2-Ag nanozyme with enhanced antibacterial ability - Wei, Feng (Chemical engineering journal (Lausanne, Switzerland : 1996), 2021)
© 2020 Elsevier B.V. All rights reserved.